Synthetic sulfoglycolipids targeting the serine–threonine protein kinase Akt. Issue 16 (15th August 2016) - Costa, Barbara; Dangate, Milind; Vetro, Maria; Donvito, Giulia; Gabrielli, Luca; Amigoni, Loredana; Cassinelli, Giuliana; Lanzi, Cinzia; Ceriani, Michela; De Gioia, Luca; Filippi, Giulia; Cipolla, Laura; et al.
Graphical abstract: Abstract: The serine–threonine protein kinase Akt, also known as protein kinase B, is a key component of the phosphoinositide 3-kinase (PI3K)–Akt–mTOR axis. Deregulated activation of this pathway is frequent in human tumors and Akt-dependent signaling appears to be critical in cell survival. PI3K activation generates 3-phosphorylated phosphatidylinositols that bind Akt pleckstrin homology (PH) domain. The blockage of Akt PH domain/phosphoinositides interaction represents a promising approach to interfere with the oncogenic potential of over-activated Akt. In the present study, phosphatidyl inositol mimics based on a β-glucoside scaffold have been synthesized as Akt inhibitors. The compounds possessed one or two lipophilic moieties of different length at the anomeric position of glucose, and an acidic or basic group at C-6. Docking studies, ELISA Akt inhibition assays, and cellular assays on different cell models highlighted 1- O -octadecanoyl-2- O -β-d -sulfoquinovopyranosyl- sn -glycerol as the best Akt inhibitor among the synthesized compounds, which could be considered as a lead for further optimization in the design of Akt inhibitors.